Public opinion and cyberterrorism - Shandler, R; Kostyuk, N; Oppenheimer, H (Oxford University Press, 2023)
Research into cyber-conflict, public opinion, and international security is burgeoning, yet the field suffers from an absence of conceptual agreement about key terms. For instance, every time a cyberattack takes place, a public debate erupts as to whether it constitutes cyberterrorism. This debate bears significant consequences, seeing as the ascription of a “terrorism” label enables the application of heavy-handed counterterrorism powers and heightens the level of perceived threat among the public. In light of widespread conceptual disagreement in cyberspace, we assert that public opinion plays a heightened role in understanding the nature of cyber threats. We construct a typological framework to illuminate the attributes that drive the public classification of an attack as cyberterrorism, which we test through a ratings-based conjoint experiment in the United States, the United Kingdom, and Israel (N = 21,238 observations). We find that the public (1) refrains from labeling attacks by unknown actors or hacker collectives as cyberterrorism; and (2) classifies attacks that disseminate sensitive data as terrorism to a greater extent even than physically explosive attacks. Importantly, the uniform public perspectives across the three countries challenge a foundational tenet of public opinion and international relations scholarship that divided views among elites on foreign policy matters will be reflected by a divided public. This study concludes by providing a definitive conceptual baseline to support future research on the topic.